TDDFT Assessment of Excited State Intramolecular Proton Transfer in a Panel of Chromophore 2-Hydroxypyrene-1-Carbaldehyde (Journal of Atomic and Molecular Sciences, 2016)
Time dependent density functional theory method at the def-TZVP/B3LYPlevel was employed to investigate excited state intramolecular proton transfer (ESIPT)properties of 2-hydroxypyrene-1-carbaldehyde (HC). Our calculated results of the primarybond lengths and infrared vibrational spectroscopic information show that, uponphotoexcitation, the intramolecular hydrogen bond is significantly strengthened in $S_1$ state, which facilitates the proton transfer process effectively. Furthermore, the electrondensity distributions of frontier molecular orbitals were demonstrated to be a positivefactor for the ESIPT. By the monitor of the characteristic peaks stretching vibrationof O-H group in the IR spectra, we have further confirmed the occurrence of ESIPT.The constructed potential energy surface of the $S_1$ state has also been used to explainthe proton transfer process and evaluate the radiationless pathway, indicating that theESIPT process occurs most easily in HC molecule.